2020
DOI: 10.1371/journal.pone.0243977
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in mortality among pulmonary tuberculosis HIV co-infected adults aged 15-49 years in Kenya

Abstract: Setting Kenya, 2012–2015 Objective To explore whether there is a gender difference in all-cause mortality among smear positive pulmonary tuberculosis (PTB)/ HIV co-infected patients treated for tuberculosis (TB) between 2012 and 2015 in Kenya. Design Retrospective cohort of 9,026 smear-positive patients aged 15–49 years. All-cause mortality during TB treatment was the outcome of interest. Time to start of antiretroviral therapy (ART) initiation was considered as a proxy for CD4 cell count. Those who took l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The followup period of this study also revealed that there were 29.5% deaths among HIV/TB co-infected patients, which might be comparable with a study of Sanzana [17] and higher and lower than studies of [18][19][20][21][22][23] and [1,16,[24][25][26], respectively. In this study, female patients presented slightly higher survival time than male patients as indicated in the K-M plot of patients, which might show a comparable result with studies of Sanzana [17] and Kosgei et al [27]. The mean and median age of the co-infected patients' were 33.63 and 32 years old, respectively, which implies that youths were the most infected with HIV persons, leading to TB co-infection, since this age represents sexually active stages with a high possibility of unprotected sex or sharing drug injection equipment that are the most common modes of HIV transmission [17,28].…”
Section: Discussionsupporting
confidence: 91%
“…The followup period of this study also revealed that there were 29.5% deaths among HIV/TB co-infected patients, which might be comparable with a study of Sanzana [17] and higher and lower than studies of [18][19][20][21][22][23] and [1,16,[24][25][26], respectively. In this study, female patients presented slightly higher survival time than male patients as indicated in the K-M plot of patients, which might show a comparable result with studies of Sanzana [17] and Kosgei et al [27]. The mean and median age of the co-infected patients' were 33.63 and 32 years old, respectively, which implies that youths were the most infected with HIV persons, leading to TB co-infection, since this age represents sexually active stages with a high possibility of unprotected sex or sharing drug injection equipment that are the most common modes of HIV transmission [17,28].…”
Section: Discussionsupporting
confidence: 91%
“…The systematic review included one study from Kenya. However, the included study was limited to smearpositive pulmonary TB patients aged 15 to 49 years only [24]. Another systematic review included 31 studies from Sub-Saharan Africa published from July 2008 to June 2018.…”
Section: Introductionmentioning
confidence: 99%
“…HIV was also independently associated with increased risk of mortality among patients on TB treatment. Previous studies within Kenya 14 , 17 , 21 and other high TB burden countries including Tanzania 15 , Zimbabwe 22 and South Africa 42 have similarly found HIV to pose a serious mortality risk among TB patients. Predictors of mortality among the HIV positive subgroup included smoking, severe malnutrition, severe illness and comorbidities.…”
Section: Discussionmentioning
confidence: 88%
“…This is despite rigorous intervention programs such as use of molecular and culture methods for TB diagnosis, use of short-course fixed dose combination drugs, nutritional support, TB/HIV collaboration and routine follow up of patients 12 . Although several studies [13][14][15][16][17] concur on the need for a person-centered interven-tion integrated within a multi-sectoral strategy, there still exists scanty information on reasons for often observed survival distributions and causes of increased risk for mortality among patients on TB treatment. Such infor-mation is useful for more accurate prediction of risks and occurrence of mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation